CeO2‐Catalyzed C‐H Functionalization of N‐Aryltetrahydroisoquinolines: An Aerobic Cross‐Dehydrogenative Coupling Reaction between Two sp3 C‐H Bonds. Issue 15 (22nd September 2016) - Sharma, Kumud; Borah, Ashwini; Neog, Kashmiri; Gogoi, Dr Pranjal
Abstract: CeO2 has been used as heterogeneous catalyst for carbon‐carbon bond formation via cross‐dehydrogenative coupling (CDC). It works efficiently for oxidative C−C bond formation between N ‐aryltetrahydroisoquinoline derivatives and a carbon nucleophile nitroalkane and acetone under aerobic conditions. This is the first report of CeO2 as a low temperature catalyst for the carbon‐carbon bond formation reaction between two sp3 C−H bonds. Abstract : CeO2 has been used as heterogeneous catalyst for carbon‐carbon bond formation via cross‐dehydrogenative coupling (CDC). It works efficiently for oxidative C−C bond formation between N ‐aryltetrahydroisoquinoline derivatives and a carbon nucleophile nitroalkane and acetone under air. This is the first report of CeO2 as a low temperature catalyst for the carbon‐carbon bond formation reaction between two sp 3 C−H bonds.